Toddler Massage as a Supplementary Intervention in Overcoming Stunting in Children: Research from Stunting Locus Area in Gorontalo City - Fatmah Zakaria; Sri Mulyaningsih; Dwi Nur Octaviani Katili; Rizky Nikmathulhusna Ali; Mohamad Rodi Isa; Herbawati Herbawati (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Stunting defined as impaired linear growth resulting in a child’s height falling below the age-appropriate standard, remains a pressing global health concern due to its long-term implications on development and increased risk of mortality. In Gorontalo Province, Indonesia, the prevalence of stunting exceeds the national target of 23.8%, with North Gorontalo Regency reporting the highest rate at 29.3%. This study aimed to examine the effect of toddler massage on weight gain among stunted children. A quasi-experimental design with a pretest-posttest control group approach was employed, involving 32 stunted toddlers selected through purposive sampling. Participants were equally allocated into an intervention group (n=16), which received toddler massage based on standard operating procedures, and a control group (n=16), which did not receive the intervention. Body weight was measured using digital scales. The results of the paired t-test revealed a statistically significant weight gain in the intervention group (p = 0.00), whereas no significant difference was observed in the control group (p = 0.164). The findings indicate that toddler massage may contribute to weight improvement in stunted children and could be considered a supportive non-pharmacological intervention in stunting management programs.